Multiculturalism and the Paradigm Shift in Counselling: Controversies and Alternative Futures - Pedersen, Paul B. (Canadian Journal of Counselling and Psychotherapy, 2007)
The fields of psychology and particularly of counselling are in the process of a paradigm shift. While there is some confusion and disagreement about the direction of that paradigm shift, there is almost universal agreement that profound changes are taking place in the field of psychology. This article suggests that these changes are being mediated by multicultural perspectives and controversies. This article also suggests that a culture-centred perspective for the future will emerge from the present confusion as a "fourth force" to complement and strengthen the three conventional theories of psychodynamism, humanism, and behaviourism.